A Comparison of Sport Commitment in Female-Only versus Co-Recreational Intramural Basketball Leagues. Issue 2 (October 2014) - Baghurst, Timothy; Tapps, Tyler; Judy, Arianne
Although there are a variety of positive benefits of collegiate intramural sports participation, female participation remains low in comparison with male participation. Discovering more about the feelings women have toward intramural sports may improve strategies for their recruitment and retention. Therefore, the purpose of this study was to investigate female students' commitment to intramural sports participation to determine whether an all-female league might foster greater levels of sport commitment than a corecreational league. Participants were 109 women from either an all-female ( n = 53) or corecreational ( n = 56) intramural basketball league who were asked to complete the Sport Commitment Model (SCM). The SCM measures constructs of Sport Commitment, Sport Enjoyment, Personal Investments, Social Constraints, Involvement Opportunities, Involvement Alternatives, and Social Support. Participants were recruited for a three-week period toward the end of the regular basketball season. Mean scores for constructs indicated that both groups were highly committed to intramural participation, indicating that sports had perceived value. Paired samples t tests found no significant differences on subscale scores between groups except for the Sport Commitment subscale, where female-only participants had significantly higher levels of Sport Commitment, t (53) = 2.10, p = .04. Female-only groups may develop greater connectedness among teammates in addition to recognizing the need for commitment throughout the season. Further analysis and recommendations for future research into women's participation in intramural sports are discussed to build upon the limited body of knowledge that exists.